2002
DOI: 10.1111/j.1523-1755.2002.kid558.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubulointerstitial injury in weanling rats with hyperhomocysteinemia

Abstract: These results indicate that diet-induced chronic hyperhomocysteinemia could induce vascular remodeling and tubulointerstitial injury in the kidney, and that these changes were ameliorated by folate supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 31 publications
4
43
1
Order By: Relevance
“…However, excess intake of methionine is highly toxic to both young and adult mammals, and this toxicity far exceeds that produced by the excessive intake of any other amino acid (Harper et al 1970). Merely doubling the normal methionine intake has been shown to result in a variety of adverse outcomes including growth retardation (Benevenga et al 1976), anemia (Yokota et al 1978, vascular damage (Troen et al 2003), kidney damage and specific hypertrophy of the tubules (Kumagai et al 2002), changes in acinar pancreatic cells and iron accumulation in liver and spleen (Ekperigin and Vohra 1981). Similar changes in liver, kidney and spleen have also been observed in human patients with methioninemia (Goldfischer et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…However, excess intake of methionine is highly toxic to both young and adult mammals, and this toxicity far exceeds that produced by the excessive intake of any other amino acid (Harper et al 1970). Merely doubling the normal methionine intake has been shown to result in a variety of adverse outcomes including growth retardation (Benevenga et al 1976), anemia (Yokota et al 1978, vascular damage (Troen et al 2003), kidney damage and specific hypertrophy of the tubules (Kumagai et al 2002), changes in acinar pancreatic cells and iron accumulation in liver and spleen (Ekperigin and Vohra 1981). Similar changes in liver, kidney and spleen have also been observed in human patients with methioninemia (Goldfischer et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Kumagai et al [10]demonstrated renal interstitial injury in hyperhomocysteinemic rats; however, an effect of Cys on renal cells could not be excluded, as hyperhomocysteinemia is inevitably associated with a rise in Cys secondary to metabolism in the body. Thus, the effects of Cys and Hcy cannot be discriminated when examining cytotoxicity for renal cells in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…have shown that impaired vital organs. Diet induced chronic Hhcy also leads to alterations in cardiac and renal function [10,11] .…”
Section: Discussionmentioning
confidence: 99%